EFL Students’ Writing Style in the Script Introduction Section - Novalia Rizkanisa; Iskandar Abdul Samad; Bustami Usman (University of Muhammadiyah Prof. DR. HAMKA, 2017)
This study investigated the rhetorical pattern (RP) of the introduction section of the scripts written by Acehnese undergraduate students studying in four different universities in Aceh. The focus of this study is on three elements: placement of the thesis, patterns of idea, and metadiscourse markers of the introduction section. Literature has reported a number of findings regarding the RP; however, information about this in undergraduate level, particularly in state universities in Aceh, is still limited. This study was conducted qualitatively by employing content analysis to identify the RP. A number of introduction sections of students’ scripts from four selected universities in Aceh were collected and analysed. The result shows the dominance of the three elements in the introduction section.